Analiasis Penguatan Pendidikan Karakter dan Peningkatan Literasi Siswa Sekolah Dasar Berbasis Dongeng “Rahasia Hutan Belantara” Melalui Pembelajaran Komik Digital - Salsabila Nur Aini; Tirta Amelia Putri; Nita Rosyda Setyawan; Luthfa Nugraheni (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
Education at the elementary school level plays a fundamental role in shaping students’ character and literacy skills during their golden age of growth. However, strengthening noble character and improving literacy, especially reading interest and comprehension of stories, still face challenges so that students do not feel bored. Facing this phenomenon, the synergy between Indonesia’s as a source of moral values and local wisdom, and digital comics as a visual medium that is popular and effective in attracting reading interest, offers great potential. The folktale “Mouse Deer, the Bear, and the Secret Forest” contains relevant moral messages, while digital comics can presnt it in an interactive and easily understandable format for students. This research aims to deeply examine the potential synergy between folktales (case study “Mouse Deer, Bear, and the Secret Forest” and digital comic learning as an effective stimulus in strengthening character education and improving literacy among elementary school students. Using a qualitative approach, this research will explore how the integration of these two media can be implemented and its impact on instilling character values through the moral messages in the story, as well as developing literacy skills through an engaging visual-verbal format for students. It is hoped that this learning model can be an innovative alternative solution in achieving the goals of character edutation and literacy in elementary schools.